The complete Mediterranean cookbook : 500 vibrant, kitchen-tested recipes for living and eating well every day (Americas Test Kitchen, 2021)
Bring the Mediterranean--from Italy and Greece, to Morocco and Egypt, to Turkey and Lebanon--into your kitchen with more than 500 fresh, flavorful recipes. This comprehensive cookbook brings the famously healthy Mediterranean diet to home cooks with a wide range of classic and inspired recipes, many fast enough to be made on a weeknight, using powerhouse Mediterranean ingredients available at your local supermarket.